Bolus-Infusion Delays of Alteplase during Thrombolysis in Acute Ischaemic Stroke and Functional Outcome at 3 Months - Paul Acheampong; Margaret T. May; Gary A. Ford; Anand K. Dixit (Stroke Research and Treatment, 2014)
Background. The efficacy of alteplase in acute ischaemic stroke (AIS) is highly time dependent. Hence, alteplase is administered as soon as possible with a bolus followed by an infusion. Delays between bolus and infusion may occur, but the extent of these delays and the impact on outcome are unclear. Aims. We investigated the extent of bolus-infusion delays and the relationship between delays and stroke outcome. Method. We reviewed medical records of 276 patients who received alteplase for AIS at our centre between April, 2008, and June, 2013. Complete demographic and clinical data including 3-month modified Rankin Score (mRS) from 229 patients were analysed comparing delays of 0–8 and >8 minutes. Results. Overall mean (SD) bolus-infusion delay was 9 (7) minutes. Baseline characteristics were similar apart from more severe strokes in delays >8 minutes. Three-month outcomes were not significantly different although delays >8 minutes had lower functional independence rate (mRS 0-1: 23.1% versus 28.1%; adjusted OR 1.2 (95% CI 0.6 to 2.4, P=0.68)) and higher mortality rate (18% versus 11%, OR 1.0, 95% CI 0.6 to 1.7, P=0.95). Conclusions. In this single centre series, bolus-infusion delays of alteplase in AIS were common and no effect of bolus-infusion delays on independence and mortality was found.